A study on factors effecting frequency of absenteeism among students in UiTM Alor Gajah Campus Melaka / Nasir Nordin...[et.al] - Nordin, Nasir; Hashim, Rozalli; Dolah, Azizah; Zainuddin, Asmah; Mohd Bee, Aida Azlina (Unit Penyelidikan dan Perundingan, 2002)
This study looks at factors that influence student frequency of absenteeism in a university setting. Twenty variables categorized into nine groups are examined, namely; gender, commuting, timetable, courses attended, assignments and tests, extra-curricular activities, health, social influence and academic performance.